A System for the Formation of Aesthetic and Pedagogical Culture in Future Teachers - Ergashev Rustam (Peerian Journals Publishing, 2024)
The development of aesthetic and pedagogical culture is crucial for future teachers as it enhances their ability to create an engaging and stimulating learning environment. This article presents a comprehensive system for the formation of aesthetic and pedagogical culture in aspiring educators. The system incorporates various strategies, approaches, and practices that contribute to the holistic development of future teachers, fostering their artistic sensibility, creativity, and pedagogical skills. By integrating aesthetic and pedagogical elements, this system aims to cultivate educators who can inspire and motivate learners, ultimately promoting a wellrounded educational experience
Keywords: Aesthetic Culture; Pedagogical Culture; Future Teachers; Artistic Sensibility